The Influence of Additional Tax Levies by Specific Percentages (Opsen) on Enhancing Regional Revenue Planning - Catur Hariyadi (Jurnal Indonesia Sosial Sains, 2024)
This research aims to analyze the effect of the implementation of the Additional Tax Levy According to a Certain Percentage (Opsen) on the increase in Regional Original Revenue (PAD) and its effectiveness in supporting regional financial planning. The research method used is quantitative with a descriptive and causal approach, involving selected regions that implement the tax opsen policy. The results showed that the implementation of tax opsen significantly increased PAD, with the contribution varying depending on the economic characteristics of each region. In addition, this study also found that tax opsens positively contributed to the stability of local financial planning. Regions that implemented tax opsen had lower PAD variability (12%) and less dependence on central transfers (25%) compared to regions without tax opsen. These findings suggest that tax opsen not only increases revenue, but also reduces local dependence on central transfers, allowing local governments to allocate resources more effectively to development programs. This research is expected to serve as a reference in the development of a more independent and sustainable fiscal policy at the local level.